Seismic assessment of rc structures with infill masonry panels in Nepal: sensitivity analysis - Chaulagain, Hemchandra (2014)
Reinforced concrete (RC) buildings in Nepal are constructed as RC frames with masonry infill panels. These structures exhibit a highly non-linear inelastic behaviour resulting from the interaction between the masonry infill panels and the surrounding frames. In this context, the paper presents an extensive case study of existing RC-framed buildings in a high seismic risk area in Nepal. A sensitivity analysis of the structures with masonry infill is performed. For this, the influence of different material properties is studied, namely diagonal compressive stress, modulus of elasticity and tensile stress of masonry infill panels. Result shows the influence on the structural behaviour particularly by variation of the diagonal compressive strength of infill masonry panels.